2017
DOI: 10.4236/ojmsi.2017.51002
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Model for Two-Spotted Spider Mites System: Verification and Validation

Abstract: This paper presents and compares four mathematical models with unique spatial effects for a prey-predator system, with Tetranychus urticae as prey and Phytoseiulus persimilis as predator. Tetranychus urticae, also known as two-spotted spider mite, is a harmful plant-feeding pest that causes damage to over 300 species of plants. Its predator, Phytoseiulus persimilis, a mite in the Family Phytoseiidae, effectively controls spider mite populations. In this study, we compared four mathematical models using a numer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
2
0
2
Order By: Relevance
“…Figure 1 clearly shows a dramatic drop of both predator and prey on all plants, causing local extinctions of spider mites and/or predatory mites. In addition, the "hump" caused by the carrying capacity of the crop was expected (Rosenzweig & MacArthur 1963), as it was included in other spider mite models (Kozlova et al 2005;Kuang et al 2017), but was not observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 clearly shows a dramatic drop of both predator and prey on all plants, causing local extinctions of spider mites and/or predatory mites. In addition, the "hump" caused by the carrying capacity of the crop was expected (Rosenzweig & MacArthur 1963), as it was included in other spider mite models (Kozlova et al 2005;Kuang et al 2017), but was not observed.…”
Section: Discussionmentioning
confidence: 99%
“…A good example of this is the well-studied predatory mite Phytoseiulus persimilis (Athias-Henriot) (Acari: Phytoseiidae) and its prey, two-spotted spider mite Tetranychus urticae (Koch) (Acari: Tetranychidae). Several predator-prey models have been developed in the past (Bernstein 1985;Bancroft and Margolies, 1999;Kozlova et al 2005;Kuang et al 2017), but validation in practical conditions is missing. E.g.…”
Section: Introductionmentioning
confidence: 99%
“…Отметим, что в настоящее время гипотеза о пропорциональности ускорения хищников градиенту плотности жертв успешно используется во многих исследованиях [4][5][6][7][8][9][10]. Модели, построенные на данном предположении, демонстрируют сложную пространственновременную динамику [4][5][6][7][8][9][10].…”
Section: Introductionunclassified
“…Отметим, что в настоящее время гипотеза о пропорциональности ускорения хищников градиенту плотности жертв успешно используется во многих исследованиях [4][5][6][7][8][9][10]. Модели, построенные на данном предположении, демонстрируют сложную пространственновременную динамику [4][5][6][7][8][9][10]. Обратим внимание, что рассматриваемая модель относится к системам с кросс-диффузией, в которых волновые явления существенно отличаются от поведения волн в системах типа "реакция-диффузия" [11][12], и которые активно используются для изучения процессов структурообразования в последнее время [13][14][15].…”
Section: Introductionunclassified